2014
DOI: 10.1111/bjd.12910
|View full text |Cite
|
Sign up to set email alerts
|

First randomized trial on clobetasol propionate and mometasone furoate in the treatment of vulvar lichen sclerosus: results of efficacy and tolerability

Abstract: Clobetasol propionate and MMF appeared similarly efficacious and well tolerated for the treatment of VLS and both may represent the first-line treatment for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 24 publications
2
70
0
2
Order By: Relevance
“…Accordingly, in our series, mean itching and burning decreased significantly after treatment. Even though less evidently than the symptoms, VLS clinical features have been reported to improve with corticosteroid treatment as well …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in our series, mean itching and burning decreased significantly after treatment. Even though less evidently than the symptoms, VLS clinical features have been reported to improve with corticosteroid treatment as well …”
Section: Discussionmentioning
confidence: 99%
“…Even though a definitive cure does not exist, the ideal treatment for VLS should aim at inducing relief of symptoms, reversing signs and preventing further anatomical changes. Topical potent and ultrapotent corticosteroids are the treatment of choice [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…In a comparative trial, 54 women were randomized to apply either CP 0.05% ointment or MMF 0.1% ointment for 12 weeks on a tapering regimen. 4 We found that CP and MMF have similar efficacy and safety in treating active VLS, both resulting effective in improving symptoms and signs of the disease and well tolerated. Almost 90% of treated patients were considered as responders with both CP and MMF treatment, without significant differences between the 2 treatments.…”
mentioning
confidence: 67%